THE INFLUENCE OF DIAPHRAGM BREATHING ON THE STATE OF THE VESSEL ENDOTHELIUM IN YOUNG WOMEN WITH ESSENTIAL HYPERTENSION - Strakolyst, H. M.; Bohdanovska, N. V.; Bessarabova, O. V. (Rehabilitation and Recreation, 2023)
The article examines one of the links of the pathogenesis of arterial hypertension – vascular endothelium dysfunction, and diaphragmatic breathing as a method of influencing and preventing essential hypertension in young women. It is noted that hypoproduction of nitric oxide and decreasing in its activity is occurred in hypertensive disease. NO plays a key role in the regulation of vascular tone in the circulatory system. Involutional changes in the vascular wall lead to decreasing of nitric oxide concentration, which complicates the course of hypertensive disease. Complications of hypertensive disease affect various systems and target organs of the body. A long-term increasing of blood pressure leads to persistent morpho-functional changes. The purpose of the study is to assess the effect of diaphragmatic breathing on the state of the vascular endothelium in young women with essential hypertension at the workplace and to provide recommendations for preventing the development of essential hypertension in the specified social group. Research material and methods: analysis of scientific and methodological literature and information sources on the research topic; instrumental methods of research; methods of assessing the functional state of the endothelium of the vessels of the subjects (n=28); methods of mathematical statistics. The results. The importance of diaphragmatic breathing as a method of healing and prevention of many diseases is shown. It is emphasized that the peculiarity of breathing is the interaction of movements with respiratory cycles and this is connected with both biomechanical and biochemical processes. The dynamics of the studied parameters were analyzed: blood pressure, heart rate, NO content by the total concentration of its stable metabolites, diameter of the brachial artery, linear velocity of blood flow, volume velocity of blood flow and their increase in the sample with reactive hyperemia. Against the background of hypertension, the deficiency of NO increases vasoconstrictor reactions, which are associated with a shift in NO. It has been proven that during correct diaphragmatic breathing, the work of the endothelium is optimized, NO and its stable metabolites are hyperproduced, which contributes to the dilation of blood vessels and a significant decrease in blood pressure. Conclusions. It is recommended to use diaphragmatic breathing as a method of influencing on the vascular endothelium condition and as a preventing method of the essential hypertension development in young women aged 25-35. Diaphragmatic breathing cannot replace physical exertion, but it can be an alternative for people who, for various reasons, cannot do aerobic training to improve the vascular endothelium condition.